##### 4.20.21 $$\left (3 x^2-2 y(x)^2\right ) y'(x)+x y(x) y'(x)^2-6 x y(x)=0$$

ODE
$\left (3 x^2-2 y(x)^2\right ) y'(x)+x y(x) y'(x)^2-6 x y(x)=0$ ODE Classiﬁcation

[_separable]

Book solution method
No Missing Variables ODE, Solve for $$y'$$

Mathematica
cpu = 0.174737 (sec), leaf count = 49

$\left \{\left \{y(x)\to c_1 x^2\right \},\left \{y(x)\to -\sqrt {-3 x^2+2 c_1}\right \},\left \{y(x)\to \sqrt {-3 x^2+2 c_1}\right \}\right \}$

Maple
cpu = 0.082 (sec), leaf count = 35

$\left [y \left (x \right ) = x^{2} \textit {\_C1}, y \left (x \right ) = \sqrt {-3 x^{2}+\textit {\_C1}}, y \left (x \right ) = -\sqrt {-3 x^{2}+\textit {\_C1}}\right ]$ Mathematica raw input

DSolve[-6*x*y[x] + (3*x^2 - 2*y[x]^2)*y'[x] + x*y[x]*y'[x]^2 == 0,y[x],x]

Mathematica raw output

{{y[x] -> x^2*C[1]}, {y[x] -> -Sqrt[-3*x^2 + 2*C[1]]}, {y[x] -> Sqrt[-3*x^2 + 2*
C[1]]}}

Maple raw input

dsolve(x*y(x)*diff(y(x),x)^2+(3*x^2-2*y(x)^2)*diff(y(x),x)-6*x*y(x) = 0, y(x))

Maple raw output

[y(x) = x^2*_C1, y(x) = (-3*x^2+_C1)^(1/2), y(x) = -(-3*x^2+_C1)^(1/2)]